Technological Scheme of a Solid Oxide Fuel Cell – Microturbine Hybrid Power Plant for Electricity Production - Antonina A. Filimonova, Andrey A. Chichirov, Alexander V. Pechenkin, Artem S. Vinogradov (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Researchers from all over the world are studying environmentally friendly, resource-saving, efficient technologies. Hydrogen fuel is recognized as one of the most promising energy resources in the near future. Hybrid power plants make it possible to use hydrogen fuel in the most efficient way. The structure of hybrid power plants includes an electrochemical plant and a mechanical generator. Thus, the solid oxide fuel cell (SOFC) works in conjunction with the gas microturbine. Hybrid power plants have high efficiency of about 60-70%. Another important advantage is the possibility of recycling hydrogen-containing gases (gaseous waste from industrial enterprises) instead of burning in the atmosphere. The purpose of the article is to develop a technological scheme of a hybrid power plant, including a 1 kW SOFC and a 30 kW gas turbine, and to calculate its technological parameters, flows and connections. The hybrid power plant is equipped with additional carbon dioxide capture technologies to achieve decarbonization of the energy production process.